Podejście procesowe w zarządzaniu : geneza i kierunki rozwoju koncepcji - Jokiel, Grzegorz (A Process Approach in Management : Concept Origins and Evolution, 2009)
In a synthetic way the article presents: the premises and origin of the process approach in management, the evolution of the concept in managerial theory and practice, perspectives on the directions of evolution and research requirements for process management in a changing economic environment. The main goal for the retrospective, organizing description of the process approach in management is to stimulate a discussion about the essence of process approach, its applications in practice and areas for improvement. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 52, s. 15-22